Comparative evaluation of the strength characteristics of light polymerization composites for teeth restoration by the three-point bend method - Kukhta, В. С.; Makeyev , В. Ф.; Kyrmanov, О. С.; Stankevych, О. М. (Actual Dentistry, 2022)
Purpose: to carry out a comparative analysis of the strength characteristics of composites of swiil polymerization for the restoration of teeth using the threepoint bending method. Results. It was determined that in terms of bending strength, dental composites were arranged in the following order: Tetric N-Ceram (164.44 MPa) < Charisma Classic (141.19 MPa) < Filtek Z250 (129.38 MPa) < Latelux (60.75 MPa). According to the Tukey criterion, the bending strength of the Latelux composite is statistically significantly different from other materials (p < 0.01). At the same time, between the fracture load of composites Tetric N-Ceram and Charisma Classic (p > 0.2), Charisma Classic and Filtek Z250 (p > 0.09), Tetric N-Ceram and Filtek Z250 (p > 0.8) this difference is not significant. Conclusion. In terms of bending strength parameters and elastic modulus, the studied materials meet modern requirements for the strength of hybridmaterials, and the Tetric N-Ceram composite has the best performance.